Majelis Ta’lim sebagai Lembaga Pendidikan Islam Non Formal di Indonesia - Karlina Putri; Nurul Azizah; Karima Karima; Gusmaneli Gusmaneli (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Majelis ta’lim is a non-formal Islamic educational institution that has its own curriculum, is held regularly, and is attended by relatively large congregations. It aims to build polite and harmonious relationships between humans and Allah SWT, humans and others, and the environment, fostering a community that is devoted to Allah SWT. The majlis ta’lim system has developed since the beginning of the spread of Islam in the Arabian continent, then spread throughout the Islamic world in Asia, Africa, and Indonesia, especially those that continue to grow today with the main mission of teaching Islam to Muslims. Even in Indonesia, the majlis ta’lim is a component of national education activities. The role of the ta’lim assembly in society is to strengthen the foundation of human life in the field of Islam in order to improve the quality of life integrally, physically and spiritually, worldly and spiritually, in accordance with Islamic teachings, namely faith and piety, which underlie life in the world and all areas of its activities. This research is library research by collecting various information from books and journals. This article explains the meaning, development, and role of the Majlis Ta’lim as a non-formal Islamic educational institution in Indonesia.